2020
DOI: 10.1371/journal.pgen.1008615
|View full text |Cite
|
Sign up to set email alerts
|

The SNAP hypothesis: Chromosomal rearrangements could emerge from positive Selection during Niche Adaptation

Abstract: The relative linear order of most genes on bacterial chromosomes is not conserved over evolutionary timescales. One explanation is that selection is weak, allowing recombination to randomize gene order by genetic drift. However, most chromosomal rearrangements are deleterious to fitness. In contrast, we propose the hypothesis that rearrangements in gene order are more likely the result of selection during niche adaptation (SNAP). Partial chromosomal duplications occur very frequently by recombination between d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 81 publications
1
27
0
Order By: Relevance
“…Subsequently, the asymmetrical loss of duplicate genes can lead to alterations in the gene order on the chromosome ( fig. 7 ) ( Brandis and Hughes 2020 ). Segmental duplications are probably the most common type of mutations in the bacterial genome as they appear at very high frequencies even in the absence of selection ( Anderson and Roth 1977 ; Haack and Roth 1995 ; Reams et al 2010 ), are often found during laboratory selection conditions ( Riehle et al 2001 ; Knöppel et al 2016 ), and play a role in shaping genome diversification and the evolution of new genes ( Bergthorsson et al 2007 ; Näsvall et al 2012 ; Zhou et al 2012 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the asymmetrical loss of duplicate genes can lead to alterations in the gene order on the chromosome ( fig. 7 ) ( Brandis and Hughes 2020 ). Segmental duplications are probably the most common type of mutations in the bacterial genome as they appear at very high frequencies even in the absence of selection ( Anderson and Roth 1977 ; Haack and Roth 1995 ; Reams et al 2010 ), are often found during laboratory selection conditions ( Riehle et al 2001 ; Knöppel et al 2016 ), and play a role in shaping genome diversification and the evolution of new genes ( Bergthorsson et al 2007 ; Näsvall et al 2012 ; Zhou et al 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…The subsequent loss of duplicate genes/operons is a slow process enabling the bacteria to adapt to potential negative consequences caused by the novel gene order. Thus, the SNAP model could explain the observed operon cluster alterations by combining high-frequency events and overcoming counter-selective barriers ( Brandis and Hughes 2020 ). This model could also explain the duplicate section of the operon cluster ( rpmJ - rpsM - rpsK - rpsD - rpoA - rplQ ) found in P .…”
Section: Resultsmentioning
confidence: 99%
“…These events are largely detrimental for free-living bacteria and are expected to be selected against (Darling et al, 2008). On the other hand, in a new environment, non-homologous recombination and the associated functional changes may provide a base for adaptation (Yan et al, 2018;Brandis and Hughes, 2020). For instance, Burkholderia mallei, a young obligate intracellular pathogen, has lost numerous clusters of genes through IS-mediated elimination as demonstrated by the comparison of its genome to strains of the ancestral species, Burkholderia pseudomallei (Losada et al, 2010;Bochkareva et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%
“…These events are largely detrimental for free-living bacteria and are expected to be selected against (18). On the other hand, in a new environment, non-homologous recombination and the associated functional changes may provide a base for adaptation (46, 47). For instance, Burkholderia mallei , a young obligate intracellular pathogen, has lost numerous clusters of genes through IS-mediated elimination as demonstrated by the comparison of its genome to strains of the ancestral species, Burkholderia pseudomallei (48, 49).…”
Section: Discussionmentioning
confidence: 99%